Effect of Pheromone Blend Components, Sex Ratio, and Population Size on the Mating of Cadra cautella (Lepidoptera: Pyralidae). Issue 6 (30th November 2020) - Sammani, Abeysinghe Mudiyanselage Prabodha; Dissanayaka, Dissanayaka Mudiyanselage Saman Kumara; Wijayaratne, Leanage Kanaka Wolly; Morrison, William Robert
Abstract: The almond moth Cadra cautella (Walker), a key pest of storage facilities, is difficult to manage using synthetic chemicals. Pheromone-based management methods remain a high priority due to advantages over conventional management practices, which typically use insecticides. Cadra cautella females release a blend of pheromone including ( Z, E )-9, 12-tetradecadienyl acetate (ZETA) and ( Z )-9-tetradecadien-1-yl acetate (ZTA). The effect of these components on mating of C. cautella and how response varies with the population density and sex ratio remain unknown. In this study, the mating status of C. cautella was studied inside mating cages under different ratios of ZETA and ZTA diluted in hexane and at different population sizes either with equal or unequal sex ratio. The lowest percentage of mated females (highest mating disruption [MD] effects), corresponding to roughly 12.5%, was produced by a 5:1 and 3.3:1 ratio of ZETA:ZTA. Populations with equal sex ratio showed the lowest percentage of mated females, at 20% and 12.5% under lower and higher density, respectively. The next lowest percentage of mated females was produced when the sex ratio was set to 1: 2 and 2:1 male:female, with just 25% and 22.5% of moths mated, respectively. This study shows that mating status of C. cautella is influenced by ZETA:ZTA ratio, sex ratio, and population size. This current knowledge would have useful implications for mating disruption programs.